Visualization and hotspot analysis of CAR‐T research based on CiteSpace - Kejin Li; Yue Teng; Weiyan Tang; Liuliu Zhang; Xiaoxu Zhi; Wenjuan Li; Jianqiu Wu (Precision Medical Sciences)
Abstract Through bibliometric analysis of CAR‐T research hotspots and development trends, a reference is provided to promote cutting‐edge research on CAR‐T. Acquired research literature on CAR‐T cells from the Web of Science Core Collection (WOSCC) as of November 20, 2023, and utilized CiteSpace software to conduct bibliometric and knowledge graph analysis. A total of 3664 articles of valid literature were obtained between 1996 and 2023. The number of publications grew slowly from 1996 to 2014 and increased sharply from 2015. In particular, from 2018 to 2022, the number of publications showed explosive growth and remained at a high level. The authors of the papers are relatively scattered, and there is little cooperation between authors. The United States has published the most papers in this field and has close cooperation with global research institutions, while China ranks second in terms of the number of papers published and has less academic cooperation or exchanges with other countries/regions. The main research hotspots include chimeric antigen receptor, immunotherapy, cytokine release syndrome, etc., which belong to two categories: the treatment mechanism and application of CAR‐T and adverse reactions and safety management. Keyword mutation analysis predicts that future research hotspots will mainly be related to technical research, safety, and post‐treatment management of CAR‐T. CAR‐T is a hot research field and is still in a rapid development stage. Domestic researchers need to strengthen exchanges and cooperation with international researchers. CAR‐T‐related technical research, safety, and post‐treatment management may be the hot spots of future research.